Analysis of the Effect of Public Accounting Firm Reputation, Profitability, Institutional Ownership, and Audit Committee on Audit Report Lag on the Indonesia Stock Exchange - Reni Dwi Widyastuti; Wilda Sari; Rizky Fahrul Yahya; Febriati Febriati (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Audit Report Lag reflects the timeliness of audited financial information and may affect the relevance of financial statements for investors and other stakeholders. Several firm and governance characteristics may influence the duration of audit completion. Objective: This study examines the effect of Public Accounting Firm (KAP) reputation, profitability, institutional ownership, and audit committee on Audit Report Lag in Consumer Services Sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Methods: This study employs a quantitative approach using secondary data obtained from companies’ annual reports and audited financial statements. The sample was selected using purposive sampling based on predetermined criteria. From 96 companies, 480 firm-year observations were initially obtained. After excluding observations with missing values and extreme outliers, 345 firm-year observations were used for multiple linear regression analysis. Results: The results show that KAP reputation, profitability, institutional ownership, and audit committee each have a negative and significant effect on Audit Report Lag. Specifically, the regression coefficients are −16.247 (p<0.001), −36.443 (p<0.001), −15.622 (p=0.003), and −13.494 (p<0.001), respectively. Conclusion: KAP reputation, profitability, institutional ownership, and audit committee effectiveness contribute to reducing Audit Report Lag. These findings indicate that audit firm capacity, favorable financial performance, stronger institutional monitoring, and effective audit committee oversight can support more timely completion of the audit process and publication of audited financial statements.